Retraction: Effect of ethylene glycol on hydrothermal formation of calcium sulfate hemihydrate whiskers with high aspect ratios. Issue 102 (21st October 2016) - Zhao, Wenpeng; Wu, Yumin; Xu, Jun; Gao, Chuanhui
Abstract : Retraction of 'Effect of ethylene glycol on hydrothermal formation of calcium sulfate hemihydrate whiskers with high aspect ratios' by Wenpeng Zhao et al., RSC Adv., 2015, 5, 50544–50548.